Transgenerational effects of short-term exposure to acidification and hypoxia on early developmental traits of the mussel Mytilus edulis. (March 2019) - Kong, Hui; Jiang, Xiaoyu; Clements, Jeff C.; Wang, Ting; Huang, Xizhi; Shang, Yueyong; Chen, Jianfang; Hu, Menghong; Wang, Youji
Abstract: Transgenerational effects of multiple stressors on marine organisms are emerging environmental themes. We thus experimentally tested for transgenerational effects of seawater acidification and hypoxia on the early development traits of the mussel Mytilus edulis . Fertilization rate, embryo deformity rate, and larval shell length were negatively impacted by acidification, while hypoxia had little effect except for increasing deformity rates under control pH conditions. Offspring from low pH/O2 parents were less negatively affected by low pH/O2 conditions than offspring from control parents; however, low pH/O2 conditions still negatively affected developmental traits in offspring from acclimated parents compared to control seawater conditions. Our results demonstrate that experimental seawater acidification and hypoxia can adversely affect early developmental traits of M. edulis and that parental exposure can only partially alleviate these impacts. If experimental observations hold true in nature, it is unlikely that parental exposure will confer larval tolerance to ocean acidification for M. edulis . Graphical abstract: Image 1 Highlights: Effects of ocean acidification and hypoxia on the early development of the mussel M. edulis were investigated. Positive carry-over effects of adult mussels exposed to low pH and hypoxia were observed on larvae performance. Low pH showed key negative effects on the early development of the mussel M. edulis.